Energy-saving film, preparation method thereof and application of energy-saving film in hollow energy-saving glass

By introducing structures such as an antioxidant protective layer, a reflective film layer, and a heat insulation functional layer into the energy-saving film, and by using modified nanomaterials and resins, the problems of insufficient light transmission and heat insulation performance of the energy-saving film have been solved, achieving efficient energy storage and improved visual comfort.

CN121471824APending Publication Date: 2026-02-06SHANGHAI BOHE TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511819413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

The light transmission and heat insulation properties of existing energy-saving films have not been further improved, resulting in increased energy consumption and reduced visual comfort.

Method used

The structure consists of an antioxidant protective layer, a substrate layer, a reflective film layer, a thermal insulation functional layer, an installation adhesive layer, and a release film layer. The reflective film layer is formed by magnetron sputtering deposition, and modified nano-titanium dioxide and graphene are used to enhance the thermal insulation performance. Modified acrylic resin is combined to improve transparency and weather resistance.

Benefits of technology

The visible light transmittance and near-infrared light blocking rate of the energy-saving film are improved, reducing energy consumption, enhancing visual comfort, and extending the service life of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of energy-saving films, and particularly relates to an energy-saving film, a preparation method thereof and application of the energy-saving film in hollow energy-saving glass. Tetrabutyl titanate is hydrolyzed through a gel method to form niobium-doped titanium gel, the niobium-doped titanium gel is calcined to form modified nano titanium dioxide, bismuth tungstate is loaded to the surface of the modified nano titanium dioxide to prepare the nano thermal insulation material, niobium is doped to replace titanium ions to initiate lattice distortion, bismuth tungstate is loaded to the surface of the modified nano titanium dioxide to form a heterojunction, and the nano thermal insulation material is prepared. The plasma resonance effect is improved by locally improving free electrons, and the near-infrared light blocking performance of the energy-saving film is further improved; the modified acrylic resin has excellent weather resistance, so that the transparent thermal insulation material is uniformly dispersed; the metal functional film is compounded in the transparent conductive oxide, so that the energy-saving film can maintain high visible light transmittance and generate a strong reflection effect on near-infrared electromagnetic waves, and the prepared energy-saving film is suitable for an environment needing high shading and heat insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy-saving film technology, specifically relating to energy-saving films, their preparation methods, and their application in insulated energy-saving glass. Background Technology

[0002] Glass, as an important material in the construction and transportation sectors, is widely used in high-rise buildings, automobiles, shop windows, and other applications. Current research shows that most building energy consumption comes from internal temperature control systems, and heat transfer through doors and windows is the primary mode of energy loss. Energy-saving films on glass can reduce indoor and outdoor heat exchange, reduce glare from sunlight, and improve visual comfort, thereby reducing energy consumption while ensuring architectural aesthetics and functionality.

[0003] Chinese invention patent CN115093801B discloses an energy-saving window film for insulated glass, its preparation method, and its application, primarily relating to the field of functional thin-film materials. The proposed method for preparing the energy-saving window film for insulated glass utilizes a high-strength base film. Metals or metal oxides / nitrides are layered and sputtered onto the surface of the high-strength base film using magnetron sputtering, reducing the infrared emissivity of the film layer. This effectively blocks infrared transmission without affecting the light transmission field of view. A modified polyurethane acrylate protective layer is applied to the surface of the formed low-emissivity layer to enhance the oxidation resistance of the coating. An adhesive layer provides adhesion to the glass and also enhances the glass's impact resistance and explosion-proof properties. When applied to insulated glass, the energy-saving window film provided by this invention possesses multiple functions, including impact resistance, thinness, energy saving, heat insulation, and oxidation resistance, thus ensuring stable performance while extending the overall service life of the energy-saving window film and its application carrier. However, existing technologies lack the technical problem of further improving the heat insulation material of the energy-saving film to enhance its light transmission and heat insulation performance. Summary of the Invention

[0004] The purpose of this invention is to provide an energy-saving film, its preparation method, and its application in insulated energy-saving glass, in order to solve the technical problem in the prior art that the light transmission and heat insulation performance of the energy-saving film have not been improved by further improving the heat insulation material of the energy-saving film.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The energy-saving film consists of an antioxidant protective layer, a substrate layer, a reflective film layer, a heat insulation functional layer, an installation adhesive layer, and a release film layer, arranged from top to bottom.

[0006] The thickness of the antioxidant protective layer is 5~8μm, and it is composed of the following components by weight: 85~90 parts polyurethane, 5~10 parts nano crack-resistant agent, 0.2~5 parts leveling agent, 3~5 parts solvent and 0.5~2 parts antioxidant 1010; The nano-crack-resistant agent is any one of nano-alumina, nano-titanium dioxide, and nano-silica; The reflective film layer is composed of aluminum-doped zinc oxide, zirconium copper aluminum nickel alloy, and aluminum-doped zinc oxide composite structure from top to bottom. The thicknesses of the three composite structures are 40~50nm, 20~30nm, and 40~50nm, respectively. The reflective film layer is formed by magnetron sputtering deposition. The chemical composition of the target material is: aluminum-doped zinc oxide ZnO:Al2O3=98~99:1~2; zirconium copper aluminum nickel alloy Zr:Cu:Al:Ni=43~44:46~47:6~7:4~5.

[0007] The thickness of the heat insulation functional layer is 15~20μm, and it is made from the following components in parts by weight: 95~100 parts modified acrylic resin, 1~2 parts nano heat insulation material, 0.5~0.8 parts graphene and 3~5 parts solvent; The thickness of the mounting adhesive layer is 8~12μm, and it is made from the following components in parts by weight: 80~90 parts polyurethane, 5~10 parts silane coupling agent KH-550 and 2~5 parts silica sol. The solvents are all one of methyl propyl ketone, isopropyl acetate, and ethyl acetate; The release film layer and the substrate layer are made of polyester (PET) film.

[0008] The preparation method of the nano-insulating material includes the following steps: S11. Prepare a mixed solvent by mixing ethanol, deionized water and nitric acid. Add niobium nitrate to the mixed solvent and stir until homogeneous to prepare a modified solution. Dissolve tetrabutyl titanate in ethanol and add it dropwise to the modified solution while stirring. Aging at room temperature, heating to react, cooling to room temperature to obtain a gel, washing the gel, drying it, and calcining it at high temperature to obtain modified nano-titanium dioxide. S12. Modified nano-titanium dioxide, bismuth nitrate pentahydrate, sodium tungstate and hexadecyltrimethylammonium bromide are added to deionized water, heated for hydrothermal reaction, the solid is collected by filtration and dried to obtain nano-insulating material.

[0009] Preferably, in S11, the volume ratio of ethanol, deionized water, and nitric acid is 40~45:5~10:1~2, the nitric acid concentration is 70~75%, the molar ratio of niobium nitrate and tetrabutyl titanate is 1~2:10~12, the reaction is carried out at 150~160℃ for 4~6 hours, washed with ethanol, dried at 60~80℃ for 4~6 hours, and calcined at 450~550℃ for 1.5~2.5 hours.

[0010] Preferably, the mass ratio of modified nano-titanium dioxide, bismuth nitrate pentahydrate, sodium tungstate, and hexadecyltrimethylammonium bromide in S12 is 5~10:4.5~5:1.2~1.5:0.25~0.5. The mixture is heated to 120~130℃ for hydrothermal reaction for 20~24h, and then vacuum dried at 50~60℃ for 1~2h. The average particle size of the obtained nano-insulating material is 40~80nm.

[0011] The preparation method of the modified acrylic resin includes the following steps: S21. Polytetrahydrofurandiol, polyether polyol, isophorone diisocyanate and dibutyltin dilaurate are added to a reactor under a nitrogen atmosphere, heated and polymerized, and 2,3-butanediol is added and mixed at high temperature to obtain a prepolymer. S22. Acrylic acid, trimethylolpropane triacrylate, and prepolymer are added to a reactor, diluted with solvent, and azobisisobutyronitrile is added. The mixture is heated to polymerize. After polymerization, triethylamine is added to neutralize the polymer. The mixture is cooled to room temperature and then solvent is added to adjust the viscosity to obtain the modified acrylic resin.

[0012] Preferably, in S21, the mass ratio of polytetrahydrofuran diol, polyether polyol, isophorone diisocyanate, dibutyltin dilaurate, and 2,3-butanediol is 232~273:100:17~20:0.2~0.6:3~5. The mixture is prepolymerized at 80~85℃ for 3~4 hours, and after adding 2,3-butanediol, the temperature is raised to 75~80℃ and mixed for 1~2 hours.

[0013] Preferably, in S22, the mass ratio of acrylic acid, trimethylolpropane triacrylate, prepolymer, solvent and azobisisobutyronitrile is 30~40:10~20:45~60:100~120:5~8, and the reaction is carried out at 75~85℃ for 10~12h; the viscosity is adjusted to 200~300mPa·s by adding solvent.

[0014] The method for preparing the energy-saving membrane includes the following steps: S1. After cleaning the substrate layer, place it in an argon atmosphere and deposit the reflective film layer by magnetron sputtering. S2. Mix modified acrylic resin, nano heat insulation material and graphene, add solvent to adjust viscosity while stirring, coat on the surface of reflective film layer, and dry to obtain heat insulation functional layer. S3. Mix polyurethane, nano crack-resistant agent, leveling agent and solvent, apply to the side of the substrate away from the reflective film layer, and dry to obtain an antioxidant protective layer. S4. Add silane coupling agent KH-550 and silica sol to an ethanol aqueous solution, heat to prepolymerize, then slowly add polyurethane and stir, coat it on the surface of the heat insulation functional layer, and dry to obtain the installation adhesive layer. S5. Align and press the release film layer with the mounting adhesive layer, then roll it up and package it to obtain the energy-saving film.

[0015] Preferably, the sputtering time in S1 is 10-15 min and the substrate rotation speed is 8-12 r / min.

[0016] Preferably, in step S2, the material is first dried at 70-80°C for 1-3 minutes, and then dried at 110-120°C for 1-3 minutes.

[0017] Preferably, in step S3, the material is first dried at 70-80°C for 1-3 minutes, and then dried at 110-120°C for 1-3 minutes.

[0018] Preferably, in the S4 ethanol-water solution, the volume ratio of ethanol to water is 1:1, the temperature is raised to 40~60℃ for prepolymerization for 20~40 min, and then dried at 70~80℃ for 1~2 h.

[0019] The application of energy-saving film in insulated glass includes the following steps: S31. Clean the glass surface, peel off the release film, and apply the energy-saving film flat to the side of the inner glass of the insulating glass closest to the air layer. Remove air bubbles by rolling to ensure tight adhesion. S32. Insulating glass is made by assembling the inner and outer glass layers of a double-glazed unit.

[0020] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention utilizes a gel method to hydrolyze tetrabutyl titanate to form niobium-doped titanium gel, which is then calcined to form modified nano-titanium dioxide. Bismuth tungstate is then loaded onto the surface of the modified nano-titanium dioxide to obtain a nano-insulating material. The modified nano-titanium dioxide provides a stable titanium-based framework, and the titanium dioxide formed by calcination at 450~550℃ has an anatase structure with a loose crystal structure and better dispersion at the nanoscale than rutile titanium dioxide. Niobium doping replaces titanium ions, inducing lattice distortion. Bismuth tungstate is loaded onto the surface of the modified nano-titanium dioxide to form a heterojunction, which locally increases the number of free electrons to enhance the plasma resonance effect and further improve the near-infrared light blocking performance of the energy-saving film.

[0021] 2. This invention utilizes the addition reaction of isophorone diisocyanate with polytetrahydrofuran diol and polyether polyol, followed by the reduction of crystallinity and improvement of prepolymer transparency through 2,3-butanediol. This results in a modified acrylic resin with excellent weather resistance, obtained by polymerizing acrylic acid, trimethylolpropane triacrylate and prepolymer. It provides a stable and dispersed carrier for transparent thermal insulation materials, ensuring uniform dispersion and facilitating the formation of defect-free films.

[0022] 3. The energy-saving film prepared by this invention is suitable for environments that require high light shading and heat insulation. The reflective film layer of this invention is a composite structure of aluminum-doped zinc oxide, zirconium copper aluminum nickel alloy, and aluminum-doped zinc oxide. By composite metal functional thin film in transparent conductive oxide, the energy-saving film can generate a strong reflection effect on near-infrared electromagnetic waves. Moreover, the thickness of the reflective film layer is much smaller than the wavelength of light, so that visible light can penetrate the film through the coupling effect, thereby maintaining a high visible light transmittance. Detailed Implementation

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] The polyether polyol involved in this invention is designated as 330N, with a molecular weight of 3000 and a hydroxyl content of 35 mgKOH / g; the silica sol is designated as JN-830; the polyurethane is designated as 1190A; and the leveling agent is designated as BYK-331.

[0025] Example 1: The energy-saving film of this example is provided with an antioxidant protective layer, a substrate layer, a reflective film layer, a heat insulation functional layer, an installation adhesive layer and a release film layer from top to bottom.

[0026] The thickness of the antioxidant protective layer is 5 μm, and it is composed of the following components: 90 g of polyurethane, 10 g of nano crack-resistant agent, 3 g of leveling agent, 3 g of solvent and 1.5 g of antioxidant 1010. The nano-crack-resistant agent is nano-alumina with an average particle size of 10 nm. The reflective film is an aluminum-doped zinc oxide, zirconium copper aluminum nickel alloy, and aluminum-doped zinc oxide composite structure with thicknesses of 50 nm, 20 nm, and 50 nm. The reflective film is formed by magnetron sputtering deposition, and the chemical composition of the target material is: aluminum-doped zinc oxide ZnO:Al2O3=98.5:1.5; zirconium copper aluminum nickel alloy Zr:Cu:Al:Ni=43:46:6:5.

[0027] The thermal insulation layer has a thickness of 15 μm and is made from the following components: 95 g of modified acrylic resin, 1.5 g of nano-thermal insulation material, 0.5 g of graphene and 3 g of solvent. The thickness of the mounting adhesive layer is 10 μm, and it is prepared from the following components: 85 g of polyurethane, 5 g of silane coupling agent KH-550 and 2.5 g of silica sol. The solvents are all ethyl acetate; the release film layer and the substrate layer are polyester films.

[0028] The preparation method of the nano-insulating material in this embodiment includes the following steps: S11. Prepare a mixed solvent by mixing 80 mL of ethanol, 20 mL of deionized water and 4 mL of 70% nitric acid. Add 0.8 g of niobium nitrate to the mixed solvent and stir until homogeneous to prepare a modified solution. Dissolve 6.8 g of tetrabutyl titanate in 20 mL of ethanol and add it dropwise to the modified solution while stirring. Aging at room temperature, heating to 150 °C and reacting for 5 h, cooling to room temperature to obtain a gel, washing the gel with ethanol, drying at 60 °C for 4 h, and calcining at 500 °C for 2 h to obtain modified nano titanium dioxide. S12. Add 5g of modified nano-titanium dioxide, 4.5g of bismuth nitrate pentahydrate, 1.3g of sodium tungstate and 0.3g of hexadecyltrimethylammonium bromide to 60mL of deionized water, heat to 120℃ and hydrothermally react for 24h, filter and collect the solid, and vacuum dry at 60℃ for 2h to obtain nano-insulating material.

[0029] The method for preparing the modified acrylic resin in this embodiment includes the following steps: S21. 255g of polytetrahydrofuran diol, 100g of polyether polyol, 18g of isophorone diisocyanate and 0.5g of dibutyltin dilaurate were added to a reactor under a nitrogen atmosphere, heated to 80℃ for prepolymerization for 4h, and then 3g of 2,3-butanediol were added and heated to 75℃ for 2h to obtain a prepolymer. S22. Add 30g of acrylic acid, 20g of trimethylolpropane triacrylate, and 60g of prepolymer to a reactor, dilute with 110g of solvent, add 6g of azobisisobutyronitrile, heat to 76℃ and react for 10h. After polymerization, add triethylamine to neutralize, cool to room temperature and add solvent to adjust the viscosity to 220mPa·s to obtain modified acrylic resin.

[0030] The method for preparing the energy-saving membrane in this embodiment includes the following steps: S1. After cleaning the substrate layer, place it in an argon atmosphere and deposit a reflective film layer by magnetron sputtering. The sputtering time is 15 min and the substrate rotation speed is 10 r / min. S2. Mix modified acrylic resin, nano heat insulation material and graphene, add solvent to adjust viscosity while stirring, coat on the surface of reflective film layer, dry at 80℃ for 3 min first, and then dry at 120℃ for 3 min to obtain heat insulation functional layer. S3. Mix polyurethane, nano crack-resistant agent, leveling agent and solvent, apply to the side of the substrate away from the reflective film layer, dry at 80°C for 3 minutes, and then dry at 120°C for 3 minutes to obtain an antioxidant protective layer. S4. Add silane coupling agent KH-550 and silica sol to a 50% ethanol aqueous solution, heat to 60℃ for prepolymerization for 20 min, then slowly add polyurethane and stir, coat it on the surface of the heat insulation functional layer, and dry it at 80℃ for 2 h to obtain the installation adhesive layer. S5. Align and press the release film layer with the mounting adhesive layer, then roll it up and package it to obtain the energy-saving film.

[0031] The application of the energy-saving film in insulated glass according to this embodiment includes the following steps: S31. Clean the glass surface, peel off the release film, and apply the energy-saving film flat to the side of the inner glass of the insulating glass closest to the air layer. Remove air bubbles by rolling to ensure tight adhesion. S32. Insulating glass is made by assembling the inner and outer glass layers of a double-glazed unit.

[0032] Example 2: The energy-saving film in this example is provided with an antioxidant protective layer, a substrate layer, a reflective film layer, a heat insulation functional layer, an installation adhesive layer, and a release film layer from top to bottom.

[0033] The thickness of the antioxidant protective layer is 7 μm, and it is composed of the following components: 88 g of polyurethane, 6 g of nano crack-resistant agent, 0.5 g of leveling agent, 5 g of solvent and 2 g of antioxidant 1010. The nano-crack-resistant agent is nano-titanium dioxide with an average particle size of 15 nm. The reflective film is an aluminum-doped zinc oxide, zirconium copper aluminum nickel alloy, and aluminum-doped zinc oxide composite structure with thicknesses of 45 nm, 25 nm, and 45 nm. The reflective film is formed by magnetron sputtering deposition, and the chemical composition of the target material is: aluminum-doped zinc oxide ZnO:Al2O3=99:1; zirconium copper aluminum nickel alloy Zr:Cu:Al:Ni=44:46:6:4.

[0034] The thermal insulation layer has a thickness of 17 μm and is made from the following components: 100 g of modified acrylic resin, 1 g of nano-thermal insulation material, 0.8 g of graphene and 5 g of solvent. The thickness of the mounting adhesive layer is 8 μm, and it is prepared from the following components: 90 g of polyurethane, 5 g of silane coupling agent KH-550 and 5 g of silica sol. The solvents are all methyl propyl ketone; the release film layer and the substrate layer are polyester films.

[0035] The preparation method of the nano-insulating material in this embodiment includes the following steps: S11. Prepare a mixed solvent by mixing 90 mL of ethanol, 10 mL of deionized water and 3 mL of 75% nitric acid. Add 0.9 g of niobium nitrate to the mixed solvent and stir until homogeneous to prepare a modified solution. Dissolve 7.2 g of tetrabutyl titanate in 10 mL of ethanol and add it dropwise to the modified solution while stirring. Aging at room temperature, heating to 155 °C and reacting for 5 h, cooling to room temperature to obtain a gel, washing the gel with ethanol, drying at 70 °C for 5 h, and calcining at 450 °C for 2.5 h to obtain modified nano titanium dioxide. S12. Add 8g of modified nano-titanium dioxide, 4.7g of bismuth nitrate pentahydrate, 1.4g of sodium tungstate and 0.5g of hexadecyltrimethylammonium bromide to 80mL of deionized water, heat to 125℃ and hydrothermally react for 20h, filter and collect the solid, and vacuum dry at 60℃ for 2h to obtain nano-insulating material.

[0036] The method for preparing the modified acrylic resin in this embodiment includes the following steps: S21. 232g of polytetrahydrofuran diol, 100g of polyether polyol, 17g of isophorone diisocyanate and 0.6g of dibutyltin dilaurate were added to a reactor under a nitrogen atmosphere, and the mixture was heated to 80°C for 4 hours for prepolymerization. Then, 3g of 2,3-butanediol was added and the mixture was heated to 75°C for 1 hour to obtain the prepolymer. S22. Add 40g of acrylic acid, 10g of trimethylolpropane triacrylate, and 50g of prepolymer to a reactor, dilute with 100g of solvent, add 7.5g of azobisisobutyronitrile, heat to 75℃ and react for 12h. After polymerization, add triethylamine to neutralize, cool to room temperature and add solvent to adjust the viscosity to 250mPa·s to obtain modified acrylic resin.

[0037] The method for preparing the energy-saving membrane in this embodiment includes the following steps: S1. After cleaning the substrate layer, place it in an argon atmosphere and deposit a reflective film layer by magnetron sputtering. The sputtering time is 10 min and the substrate rotation speed is 12 r / min. S2. Mix modified acrylic resin, nano heat insulation material and graphene, add solvent to adjust viscosity while stirring, coat on the surface of reflective film layer, dry at 70℃ for 1 min, and then dry at 110℃ for 1 min to obtain heat insulation functional layer. S3. Mix polyurethane, nano crack-resistant agent, leveling agent and solvent, apply to the side of the substrate away from the reflective film layer, dry at 70°C for 1 min, and then dry at 110°C for 1 min to obtain an antioxidant protective layer. S4. Add silane coupling agent KH-550 and silica sol to a 50% ethanol aqueous solution, heat to 40℃ for prepolymerization for 30 min, then slowly add polyurethane and stir, coat it on the surface of the heat insulation functional layer, and dry at 70℃ for 2 h to obtain the installation adhesive layer. S5. Align and press the release film layer with the mounting adhesive layer, then roll it up and package it to obtain the energy-saving film.

[0038] Example 3: The energy-saving film in this example is provided with an antioxidant protective layer, a substrate layer, a reflective film layer, a heat insulation functional layer, an installation adhesive layer, and a release film layer from top to bottom.

[0039] The thickness of the antioxidant protective layer is 8μm, and it is composed of the following components: 85g of polyurethane, 5g of nano crack-resistant agent, 5g of leveling agent, 5g of solvent and 2g of antioxidant 1010. The nano-crack-resistant agent is nano-silica with an average particle size of 12nm. The reflective film is an aluminum-doped zinc oxide, zirconium copper aluminum nickel alloy, and aluminum-doped zinc oxide composite structure with thicknesses of 40 nm, 30 nm, and 40 nm. The reflective film is formed by magnetron sputtering deposition, and the chemical composition of the target material is: aluminum-doped zinc oxide ZnO:Al2O3=98:2; zirconium copper aluminum nickel alloy Zr:Cu:Al:Ni=43:46:6.5:4.5.

[0040] The thermal insulation layer has a thickness of 120 μm and is made from the following components: 97.5 g of modified acrylic resin, 2 g of nano-thermal insulation material, 0.5 g of graphene and 3 g of solvent. The thickness of the mounting adhesive layer is 12μm, and it is prepared from the following components: 90g of polyurethane, 10g of silane coupling agent KH-550, and 4g of silica sol. The solvents are all isopropyl acetate; the release film layer and the substrate layer are polyester films.

[0041] The preparation method of the nano-insulating material in this embodiment includes the following steps: S11. Prepare a mixed solvent by mixing 80 mL of ethanol, 20 mL of deionized water and 4 mL of 75% nitric acid. Add 1 g of niobium nitrate to the mixed solvent and stir until homogeneous to prepare a modified solution. Dissolve 8 g of tetrabutyl titanate in 15 mL of ethanol and add it dropwise to the modified solution while stirring. Aging at room temperature, heating to 160 °C and reacting for 6 h, cooling to room temperature to obtain a gel, washing the gel with ethanol, drying at 80 °C for 4 h, and calcining at 550 °C for 1.5 h to obtain modified nano titanium dioxide. S12. Add 9g of modified nano-titanium dioxide, 5g of bismuth nitrate pentahydrate, 1.5g of sodium tungstate and 0.5g of hexadecyltrimethylammonium bromide to 80mL of deionized water, heat to 130℃ and hydrothermally react for 20h, filter and collect the solid, and vacuum dry at 50℃ for 1h to obtain nano-insulating material.

[0042] The method for preparing the modified acrylic resin in this embodiment includes the following steps: S21. 273g of polytetrahydrofuran diol, 100g of polyether polyol, 20g of isophorone diisocyanate and 0.6g of dibutyltin dilaurate were added to a reactor under a nitrogen atmosphere, and the mixture was heated to 85°C for 3 hours for prepolymerization. Then, 3g of 2,3-butanediol was added and the mixture was heated to 75°C for 1 hour to obtain the prepolymer. S22. Add 35g of acrylic acid, 15g of trimethylolpropane triacrylate, and 45g of prepolymer to a reactor, dilute with 100g of solvent, add 8g of azobisisobutyronitrile, heat to 75℃ and react for 12h. After polymerization, add triethylamine to neutralize, cool to room temperature and add solvent to adjust the viscosity to 280mPa·s to obtain modified acrylic resin.

[0043] The method for preparing the energy-saving membrane in this embodiment includes the following steps: S1. After cleaning the substrate layer, place it in an argon atmosphere and deposit a reflective film layer by magnetron sputtering. The sputtering time is 13 min and the substrate rotation speed is 12 r / min. S2. Mix modified acrylic resin, nano heat insulation material and graphene, add solvent to adjust viscosity while stirring, coat on the surface of reflective film layer, dry at 75℃ for 2 min first, and then dry at 115℃ for 2 min to obtain heat insulation functional layer. S3. Mix polyurethane, nano crack-resistant agent, leveling agent and solvent, apply to the side of the substrate away from the reflective film layer, dry at 75°C for 2 min, and then dry at 115°C for 2 min to obtain an antioxidant protective layer. S4. Add silane coupling agent KH-550 and silica sol to a 50% ethanol aqueous solution, heat to 50℃ for prepolymerization for 25 minutes, then slowly add polyurethane and stir, coat it on the surface of the heat insulation functional layer, and dry it at 80℃ for 2 hours to obtain the installation adhesive layer. S5. Align and press the release film layer with the mounting adhesive layer, then roll it up and package it to obtain the energy-saving film.

[0044] Comparative Example 1 differs from Example 1 in that the reflective film layer is replaced with 100nm aluminum-doped zinc oxide.

[0045] Comparative Example 2 differs from Example 1 in that the nano-insulating material is replaced with titanium dioxide with an average particle size of 40 nm.

[0046] Comparative Example 3 differs from Example 1 in that the modified acrylic resin is replaced with acrylic resin of type AC2594.

[0047] Performance testing The energy-saving films prepared in each embodiment and comparative example were applied to insulated energy-saving glass to obtain test samples.

[0048] According to GB / T 29061-2012 "Functional Films for Architectural Glass", the test samples prepared by each embodiment and comparative example were tested for the transmittance of visible light (380~780nm) and the blocking rate of near-infrared band (780~2500nm).

[0049] The test samples prepared in each embodiment and comparative example were cut into 10×10cm shapes and installed on the top of a 20×20×20cm polystyrene insulated box. The internal temperature of the insulated box was 25°C when not irradiated. A 100W infrared xenon lamp was used to irradiate the test sample vertically at a distance of 50cm from the surface of the test sample, and the temperature inside the insulated box was recorded after 40 minutes of irradiation.

[0050] The test results are shown in Table 1:

[0051] As shown in the table above, the visible light transmittance of the test samples prepared in Examples 1-3 is 74.8-75.3%, the near-infrared band blocking rate is 64.6-66.9%, and the temperature inside the heat preservation box after irradiation for 40 minutes is 36.6-37.1℃. Comparative Example 1 lacks a zirconium copper aluminum nickel alloy reflective layer, and its visible light transmittance is slightly higher than that of Example 3. However, the lack of a zirconium copper aluminum nickel alloy layer results in insufficient shielding of many near-infrared bands. Therefore, the near-infrared band blocking rate of Comparative Example 1 is 45.2%. This indicates that the energy-saving film prepared by the present invention has excellent visible light transmittance, near-infrared band blocking rate, and heat insulation performance.

[0052] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

[0053] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. Energy saving film characterized in that, From top to bottom, the anti-oxidation protective layer, the substrate layer, the reflective film layer, the thermal insulation functional layer, the mounting adhesive layer and the release film layer are sequentially arranged; The reflective film layer is sequentially arranged from top to bottom in a composite structure of aluminum-doped zinc oxide, zirconium-copper-aluminum-nickel alloy and aluminum-doped zinc oxide, and the thicknesses of the three layers are 40-50 nm, 20-30 nm and 40-50 nm respectively; the reflective film layer is formed by magnetron sputtering deposition, and the chemical composition of the target material is: aluminum-doped zinc oxide ZnO:Al2O3=98-99:1-2; zirconium-copper-aluminum-nickel alloy Zr:Cu:Al: Ni=43-44:46-47:6-7:4-5; The thermal insulation functional layer has a thickness of 15-20 microns and is prepared from the following components by mass: 95-100 parts of modified acrylic resin, 1-2 parts of nano thermal insulation material, 0.5-0.8 parts of graphene, and 3-5 parts of solvent.

2. The energy saving film of claim 1, wherein, The anti-oxidation protective layer has a thickness of 5-8 microns and is composed of the following components by mass: 85-90 parts of polyurethane, 5-10 parts of nano anti-cracking agent, 0.2-5 parts of leveling agent, 3-5 parts of solvent, and 0.5-2 parts of antioxidant 1010; The nano anti-cracking agent is any one of nano aluminum oxide, nano titanium dioxide and nano silicon dioxide; The mounting adhesive layer has a thickness of 8-12 microns and is prepared from the following components by mass: 80-90 parts of polyurethane, 5-10 parts of silane coupling agent KH-550, and 2-5 parts of silica sol; The solvent is any one of methyl propyl ketone, isopropyl acetate and ethyl acetate; The material of the release film layer and the substrate layer is polyester film.

3. The energy saving film of claim 1, wherein, The preparation method of the nano thermal insulation material comprises the following steps: S11, prepare a mixed solvent from ethanol, deionized water and nitric acid, add niobium nitrate to the mixed solvent and stir uniformly to prepare a modified solution, dissolve tetrabutyl titanate in ethanol, add it dropwise to the modified solution under stirring, age at room temperature, react under heating, cool to room temperature, wash the gel, dry, and calcine at high temperature to prepare modified nano titanium dioxide; S12, add modified nano titanium dioxide, bismuth nitrate pentahydrate, sodium tungstate and cetyltrimethylammonium bromide to deionized water, react under hydrothermal conditions, collect the solid by filtration, and dry to prepare nano thermal insulation material.

4. The energy saving film of claim 3, wherein, In S11, the volume ratio of ethanol, deionized water and nitric acid is 40-45:5-10:1-2, the concentration of nitric acid is 70-75%, and the molar ratio of niobium nitrate and tetrabutyl titanate is 1-2:10-12; the reaction is carried out at 150-160℃ for 4-6 hours, the gel is washed with ethanol, dried at 60-80℃ for 4-6 hours, and calcined at 450-550℃ for 1.5-2.5 hours.

5. The energy saving film of claim 3, wherein, In S12, the mass ratio of modified nano titanium dioxide, bismuth nitrate pentahydrate, sodium tungstate and cetyltrimethylammonium bromide is 5-10:4.5-5:1.2-1.5:0.25-0.5, the reaction is carried out under hydrothermal conditions at 120-130℃ for 20-24 hours, and the product is vacuum dried at 50-60℃ for 1-2 hours.

6. The energy saving film of claim 1, wherein, The preparation method of the modified acrylic resin comprises the following steps: S21, polytetrahydrofuran diol, polyether polyol, isophorone diisocyanate and dibutyltin dilaurate are added into a reaction kettle in a nitrogen atmosphere, polymerization is carried out by heating, 2, 3-butanediol is added and mixed at high temperature, and a prepolymer is prepared; S22, acrylic acid, trimethylolpropane triacrylate, and the prepolymer are added into a reaction kettle, a solvent is added for dilution, azobisisobutyronitrile is added, polymerization is carried out by heating, triethylamine is added for neutralization after polymerization is completed, the temperature is cooled to room temperature, a solvent is added again to adjust the viscosity, and a modified acrylic resin is prepared.

7. The energy saving film of claim 6, wherein, The mass ratio of polytetrahydrofuran diol, polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and 2, 3-butanediol is 232-273:100:17-20:0.2-0.6:3-5, pre-polymerization is carried out by heating to 80-85℃ for 3-4h, and 2, 3-butanediol is added and mixed at 75-80℃ for 1-2h after heating; the mass ratio of acrylic acid, trimethylolpropane triacrylate, the prepolymer, the solvent and azobisisobutyronitrile in S22 is 30-40:10-20:45-60:100-120:5-8, and reaction is carried out by heating to 75-85℃ for 10-12h; the viscosity is adjusted to 200-300mPa·s by adding a solvent.

8. The method of claim 1-7, wherein, The method comprises the following steps: S1, the substrate layer is cleaned and placed in an argon atmosphere, and a reflective film layer is prepared by magnetron sputtering deposition; S2, the modified acrylic resin, nano thermal insulation material and graphene are mixed, a solvent is added under stirring to adjust the viscosity, and the mixture is coated on the surface of the reflective film layer and dried to prepare a thermal insulation functional layer; S3, polyurethane, nano anti-cracking agent, leveling agent and solvent are mixed, and the mixture is coated on the side of the substrate away from the reflective film layer and dried to prepare an oxidation protection layer; S4, silane coupling agent KH-550 and silica sol are added into an ethanol aqueous solution, pre-polymerization is carried out by heating, and then polyurethane is slowly added and stirred to prepare a mounting adhesive layer; S5, the release film layer is aligned and pressed with the mounting adhesive layer, and the energy-saving film is prepared by winding and packaging.

9. Use of the energy saving film according to any one of claims 1 to 7 in a hollow energy saving glass, characterized in that, The method for preparing hollow energy-saving glass by using the energy-saving film comprises the following steps: S31, the surface of the glass is cleaned, the release film is torn off, the energy-saving film is flatly attached to the side of the inner layer glass of the hollow glass close to the air layer, air bubbles are removed by rolling to ensure close attachment; S32, the inner layer glass and the outer layer glass of the hollow glass are assembled to prepare a hollow energy-saving glass.

Citation Information

Patent Citations

  • Energy-saving window film for insulating glass and preparation method and application thereof

    CN115093801B